Herd-level risk factors for bovine tuberculosis and adoption of related biosecurity measures in Northern Ireland: A case-control study. (July 2016) - O'Hagan, M.J.H.; Matthews, D.I.; Laird, C.; McDowell, S.W.J.
Highlights: A case-control study was conducted in a high bovine tuberculosis (bTB) incidence area. Risk factors for bTB breakdown included the presence of badgers and slurry management. There was a lack of adoption of bTB related biosecurity measures. Encouragement of farmers to adopt bTB related biosecurity measures is recommended. Abstract: Bovine tuberculosis (bTB) is a zoonotic disease which is endemic in Northern Ireland. As it has proven difficult to eradicate this disease, partly due to a wildlife reservoir being present in the European badger ( Meles meles ), a case-control study was conducted in a high incidence area in 2010–2011. The aim was to identify risk factors for bTB breakdown relating to cattle and badgers, and to assess the adoption of bTB related biosecurity measures on farms. Face-to-face questionnaires with farmers and surveys of badger setts and farm boundaries were conducted on 117 farms with a recent bTB breakdown (cases) and 75 farms without a recent breakdown (controls). On logistic regression at univariable and multivariable levels, significant risk factors associated with being a case herd included having an accessible badger sett within the farm boundaries in a field grazed in the last year (odds ratio, OR, 4.14; 95% confidence interval, CI, 1.79, 9.55), observation of live badgers (OR 4.14; 95% CI 1.79, 9.55), purchase of beef cattle (OR 4.60; 95% CI 1.61, 13.13), use of contractors to spread slurry (OR 2.83; 95% CI 1.24, 6.49), feeding meal on top of silage (OR 3.55; 95% CI 1.53, 8.23) and feeding magnesium supplement (OR = 3.77; 95% CI 1.39, 10.17). The majority of setts within the farm boundary were stated to be accessible by cattle (77.1%; 95% CI 71.2, 83.0%) and 66.8% (95% CI 63.8, 69.7%) of farm boundaries provided opportunities for nose-to-nose contact between cattle. Adoption of bTB related biosecurity measures, especially with regards to purchasing cattle and badger-related measures, was lower than measures related to disinfection and washing.